"Anyone who weighs up risks doesn`t belong here": how do elite handball players manage physical health risk throughout their professional careers? - Bursik, J.; Mayer, J.; Thiel, A.; Kühnle, F.; John, J. M. (Frontiers in Sports and Active Living, 2025)
Objectives: Elite athletes frequently encounter physical health risks, such as an injury, illness or pain, which are accompanied by sociocultural norms, individual perceptions, and situational pressures. While research has explored risk management in sports, limited attention has been given to the subjective experiences of athletes managing these risks across their careers. This study addresses this gap by examining how elite handball players manage physical health risks, focusing on the role of risk perception, evaluation, and coping.